Distribuição espacial e temporal da tuberculose em povos indígenas no estado do Maranhão. - Sá, Karina Vanessa Chagas da Silva (2016)
Tuberculosis (TB) presents as a serious public health problem in the world, constituting a relevant infectious disease with high morbidity and mortality, particularly in indigenous people, considered a population at risk for having an incidence rate ten times higher if compared to the general population. Maranhão, from the point of view of the ethnic constitution of its population, has 38,831 indigenous people, distributed in 19 regional units of health. It's the objective of this study to analyze the spatial and temporal distribution of new cases of tuberculosis in indigenous in the state of Maranhão. We conducted an ecological study of historical series of new cases of TB in indigenous from 2010 to 2014 reported in the System for Notifiable Diseases Information System (SINAN). The population consisted of all new cases of tuberculosis in indigenous in the State of Maranhão , reported in the System for Notifiable Diseases Information System (SINAN), from January 2010 to December 2014. For mapping TB in indigenous was held the organization of addresses as to type of the public place,street name, house number, neighborhood, zip code, longitude, latitude, city of residence, health regional, state of residence. The results, after georeferencing of cases during the study period, were presented in thematic maps elaborated in the Geographical Information System (GIS), ArcGIS Program, version 10.1. As to the sociodemographic characteristics of the indigenous population, the highest frequency was observed in the age group of 20-39 years (38.8%), males (68.3%), with ≤8 years of study (50.0%) and residents in rural areas (74.2%); and clinical and laboratory aspects, the pulmonary form was the most frequent (94.4%) and the non-performance of the tuberculin skin test (78.7%), the positive Gram stain in the first sample (50.0%), the negativity second sample (32.0%), the non-performance of the culture (90.4%), and the negative result of HIV testing (53.4%). When evaluating TB cases per year of occurrence it was observed that 2012 (58,1 / 100.000 hab.) And 2014 (77,0 / 100,000 hab.) had the lowest incidence rates, and in 2010 (95,2 / 100,000 hab .) the highest. The areas of Regional Units of Health - RUH with the highest incidences were: Bacabal, Codó, Rosário, Pinheiro, São Luís, Itapecuru-Mirim, Balsas, Chapadinha e Presidente Dutra. It is concluded that the number of cases of TB in indigenous in Maranhao is still quite high and is distributed in RUH, especially in those presenting the highest concentration of indigenous areas, requiring the adoption of more effective measures to prevent and control the disease the indigenous population of the state.